ANALISIS PEMBIAYAN MURABAHAH PADA PERBANKAN SYARIAH DI INDONESIA - Pocut Ainiah (Jurnal Syariah dan Ekonomi Islam, 2024)
One way to collect funds from the community in Islamic banking is through financing with products available in Islamic banks, namely mudharabah, musyarakah, murabahah, salam, ishtina', qard and ijarah. However, the most dominant prima donna in Islamic banking is murabahah financing products. Murabahah financing customers have increased every year in BUS, UUS and BPRS. Islamic banking is supervised and its products are guaranteed to be in accordance with sharia by the National Sharia Council (DSN) and the Sharia Supervisory Board (DPS). So that in terms of the MUI Fatwa, murabahah financing in Indonesia that occurs in Islamic banking is in accordance with the MUI fatwa which means in accordance with the opinions of Islamic scholars.